Dietary Pattern, Anthropometric Indices and Developmental Milestone of Children Aged 6-60 Months in Peri-Urban Communities East of Nigeria - Ibeanu, Vivienne N.; Onyechi, Uchenna A.; Ani, Peace N.; Omeh, Ozioma A. (International Journal of Child Health and Nutrition, 2018)
Background: Good nutritional status is of paramount importance for a child’s physical, mental and social development after inter-uterine life. Objective: Dietary pattern, anthropometric indices and developmental milestone of children aged 6-60 months in peri-urban communities were investigated. Design: The children (236) were randomly selected from health centers and nursery schools in three selected communities. Data were collected with structured questionnaire and anthropometry. The questionnaire administered to the mothers of the children elicited information on their socioeconomic characteristics, dietary pattern and developmental milestones of the children. Anthropometric parameters of the children were measured using standard instruments and procedures. The mean length/height and weight of the children in relation to their ages were compared with WHO child growth standard. Data collected were statistically analyzed using SPSS version 16. Results: Less than 6% of the mothers introduced complementary food at 6 months, 31.4% introduced before 6 months and 63.2% after 7 months. Majority (97.5%) of the mothers enriched complementary foods with fish (73.7%), infant formular (72.9%), soybean powder (66.5%) and egg (64.0%). A total of 10.6% and 1.7% of the children were moderately and severely stunted, respectively while 4.7% of them had moderate wasting. Underweight was observed more among children within 6 – 24 months. The mean ages for sitting, crawling, standing with support and standing without support reported in this study were 6, 7, 8 and 10 months, respectively. Conclusion: Scaling up actions on optimal complementary feeding of children would go a long way in improving their nutritional status and physical development.